Kinerja Aparatur Sipil Negara Di Kantor Kecamatan Mantikulore Kota Palu - Reza, Fachrul (Sekolah Tinggi Ilmu Administrasi (STIA) Pembangunan Palu, 2024)
This research aims to determine the performance of the state civil apparatus in Matikulore sub-district, Palu city. This research uses qualitative methods with a case study approach.Meanwhile, the data analysis used in this research is data collection, data reduction, data presentation and drawing conclusions. Based on the results of research conducted regarding the performance of apparatus at the Mantikulore District Office, Palu City, Central Sulawesi Province, it can be concluded that the quality of apparatus performance at the Mantikulore District Office, Palu City, Central Sulawesi Province, can be seen from several indicators, namely: productivity, service quality, responsiveness, responsiveness, and accountability. This can be seen from the informant's answers and the researcher's observations that the aspects of service quality, responsiveness and responsiveness are still not implemented optimally in Mantikulore sub-district and in service and work time discipline must be improved further, also in administrative programs are not yet fully appropriate and performance the apparatus has not achieved maximum results. And for productivity and responsibility, it can be considered to be going quite well. The factors that influence the performance of Village Apparatus in the Mantikulore District Office, Palu City, Central Sulawesi Province that the author observed during conducting research are Human Resources and infrastructure in the office.